Estimate for Picard iterations of a Hermitian matrix operator - Akhadkulov, H.; Saaban, Azizan; Alipiah, F.M.; Jameel, A. F. (IP Publishing LLC, 2017)
The purpose of this paper is to study the Picard iterations of a Hermitian matrix operator.In [1], we proved the existence and uniqueness of attractive fixed point of an operator defined on Hermitian matrix space and satisfying a certain condition. In this paper we show that the n th Picard iterations of that Hermitian matrix operator converges to the fixed point with the rate O (n-1).